OP16 Characterization of the Clinical Features and Outcomes of Paediatric Patients with Isolated Colonic Crohn's Disease: A Multi-center Study from the Porto Group of ESPGHAN. (27th May 2021) - Berger, T; Miin Lee, H; Ramasamy Padmanaban, L; Wine, E; Yerushalmi, A; Hojsak, I; Bronski, J; Serban, D; Yogev, D; Ledder, O; Lionetti, P; Scarrallo, L; et al.
Abstract: Background: Isolated colonic (L2) Crohn's disease (CD) in adults is thought to have unique clinical and genetic features compared with ileal (L1) CD and ulcerative colitis (UC). Similar studies in paediatrics are scarce. Our goal was to characterize the clinical features of paediatric patients with isolated colonic CD and compare them to patients with ileo-cecal CD and those with UC. Methods: This was a multi-center retrospective study including 21 sites affiliated with the Porto IBD group and IBD interest group of ESPGHAN. Data of paediatric patients diagnosed between 2014–2017 with L1 or L2 CD, or with UC, was collected, including information on demographic, clinical and laboratory parameters at diagnosis, end of induction, 1 year and 3 years after diagnosis (or at last follow-up). Results: Data was collected on 300 children (102 L1, 94 L2, 104 UC) with similar demographic features. At diagnosis, bloody stools were identified in 45% of L2 patients, compared with 15% and 95% of L1 and UC patients, respectively (P<0.001), while fever was documented in 27% of L2 patients, compared to 13% and 3% of L1 and UC patients, respectively (P<0.001). At the time of diagnosis, the median pediatric Crohn's disease activity index for patients with L1 and L2 was 25 (IQR 17.5–37) and 27.5 (20–40), respectively, while the median pediatric ulcerative colitis activity index was 40 (30–55) for patients with UC. C-reactive protein levels were significantly higher among CD patients (both L1 and L2), compared to patients with UC, and calprotectin values were comparable. ASCA was positive in 55%, 25% and 2% (P<0.001) and pANCA in 2%, 17% and 53% (P<0.001) in L1, L2 and UC patients, respectively. Granulomas were identified in 36% of L2 patients, similar to patients with L1 (33%). For induction therapy, exclusive enteral nutrition, oral steroids and mesalazine were used in 50%, 45% and 38% of patients with L2 CD, compared with 72%, 28% and 9%, and 0%, 52% and 75% of L1 and UC patients, respectively (P<0.001). Steroid-free clinical remission at the end of induction was overall similar between groups, around 55%. At 1-year post-diagnosis, 62%, 68% and 40% were on an immunomodulator (P=0.03) and 41%, 26% and 22% were receiving anti-TNFα agent (P=0.01), of patients with L1, L2 and UC, respectively. While time to initiation of an anti-TNFα agent was significantly shorter in L1 patients compared with L2 and UC (P=0.03), time to admission and time to surgery were similar. Conclusion: Paediatric patients with isolated colonic CD exhibit several clinical features which differentiate them from ileo-cecal CD and UC. Prospective studies are required to understand the pathogenesis of this unique entity and define short- and long-term outcomes.